The Correlation of Regional Microstructure and Mechanics of the Cervical Articular Process in Adults - Huimei Feng (MDPI AG, 2021)
Purpose: Using micro-CT and finite element analysis to establish regional variation microarchitectures and correlation with mechanical properties of cervical articular facet trabecular bone to predict cervical spine security and material properties. Methods: A total of 144 cervical articular processes (each articular was separate to four region of interest (ROI), superior-anterior (SA), superior-posterior (SP), inferior-anterior (IA), and inferior-posterior (IP) regions) specimens with a volume of 5 × 5 × 5 mm3 were scanned by micro-CT, and allowable stress and other mechanical properties parameters in each region were calculated after mechanical testing, then the effectiveness was verified of finite element models by ABAQUS software. Results: Maximum and minimum values of C2–C7 articular processes and regions are C5 and C7 level, SA and SP regions for bone volume fraction (BV/TV) and trabecular thickness (Tb.Th), whose variation tendency is similar to the Young’s modulus, allowable stress, BMD, maximum force and strain. Between Young’s modulus and all microstructure parameters, especially between BV/TV, bone mineral density (BMD) and Tb.Th, had higher linear regression coefficients R2 = 0.5676, 0.6382, 0.3535, respectively. BMD and yield strength, BV/TV, and allowable stress also had better regression coefficients, R2 = 0.5227, 0.5259, 0.5426, respectively. Conclusions: The contribution of the microstructure and mechanical properties of the C2–C7 cervical spine to the movement of the cervical spine is different and has a good correlation and the effectiveness of the finite element model is also verified that we can correctly calculate the microstructure and mechanical properties of the cervical articular process to evaluate the stability and injury risk of cervical vertebrae by the established model.